Human Viral Oncoproteins and Ubiquitin–Proteasome System - Atani, Zahra Rafiei; Hosseini, Sareh Sadat; Goudarzi, Hossein; Faghihloo, Ebrahim (Global Medical Genetics, 2024)
Some human cancers worldwide may be related to human tumor viruses. Knowing, controlling, and managing the viruses that cause cancers remain a problem. Also, tumor viruses use ubiquitin–proteasome system (UPS) that can alter host cellular processes through UPS. Human tumor viruses cause persistent infections, due to their ability to infect their host cells without killing them. Tumor viruses such as Epstein–Barr virus, hepatitis C virus, hepatitis B virus, human papillomaviruses, human T cell leukemia virus, Kaposi's sarcoma-associated herpesvirus, and Merkel cell polyomavirus are associated with human malignancies. They interfere with the regulation of cell cycle and control of apoptosis, which are important for cellular functions. These viral oncoproteins bind directly or indirectly to the components of UPS, modifying cellular pathways and suppressor proteins like p53 and pRb. They can also cause progression of malignancy. In this review, we focused on how viral oncoproteins bind to the components of the UPS and how these interactions induce the degradation of cellular proteins for their survival.
Keywords: proteasome; UPS; ubiquitin; oncoprotein; tumor virus